Tax evasion and service-trust paradigm: A meta-analysis - Nurkholis Nurkholis (Taylor & Francis Group, 2020)
The purpose of this research is to present the results of meta-analysis on the relationship between the determinant factors against tax evasion based on service and trust paradigm. This research synthesized 102 results of 33 individual articles within a period of 1978–2017. There is a robust conclusion that the improving service quality and increasing public trust are two effective instruments in fighting against the tax evasion. As implied in the Social Contract Theory, the effect of service quality in decreasing the tax evasion is greater than that of public trust level. Considering the national culture as one potential moderating variable, the results of heterogeneity analysis suggested that the cultural aspect represented in the Hofstede’s cultural dimension had an important role as the moderating variable between service and tax evasion. This finding should be interesting for the policymakers in some points. First, the tax authorities should considerably improve the service quality to reduce the non-compliance behaviors. Second, by considering the moderating variable which influences the impact of service quality and public trust on tax evasion, each country should consider its unique national cultural values when designing the tax policies and programs.